Sediment Distribution in the Intertidal Zone of the Tay Estuary - Alizai, S.A.K. (Journal of Himalayan Earth Sciences, 1986)
The paper describes granulometric analyses of the sediments accumulating today in the intertidal zone of the Tay estuary. The significance of the grain size distribution is discussed and the composition of sediments me examined.